Shaping Metallic Nanolattices: Design by Microcontact Printing from Wrinkled Stamps. Issue 11 (24th February 2020) - Wang, Xuepu; Sperling, Marcel; Reifarth, Martin; Böker, Alexander
Abstract: A method for the fabrication of well‐defined metallic nanostructures is presented here in a simple and straightforward fashion. As an alternative to lithographic techniques, this routine employs microcontact printing utilizing wrinkled stamps, which are prepared from polydimethylsiloxane (PDMS), and includes the formation of hydrophobic stripe patterns on a substrate via the transfer of oligomeric PDMS. Subsequent backfilling of the interspaces between these stripes with a hydroxyl‐functional poly(2‐vinyl pyridine) then provides the basic pattern for the deposition of citrate‐stabilized gold nanoparticles promoted by electrostatic interaction. The resulting metallic nanostripes can be further customized by peeling off particles in a second microcontact printing step, which employs poly(ethylene imine) surface‐decorated wrinkled stamps, to form nanolattices. Due to the independent adjustability of the period dimensions of the wrinkled stamps and stamp orientation with respect to the substrate, particle arrays on the (sub)micro‐scale with various kinds of geometries are accessible in a straightforward fashion. This work provides an alternative, cost‐effective, and scalable surface‐patterning technique to fabricate nanolattice structures applicable to multiple types of functional nanoparticles. Being a top‐down method, this process could be readily implemented into, e.g., the fabrication of optical and sensing devices on a large scale. Abstract : A method is contributed for the preparation of nanoparticulate patterns onto flat surfaces. The use of wrinkled polydimethylsiloxane stamps for patterning renders this microcontact printing method fast, cost effective, and easy to apply to various kinds of flat silicon‐based surfaces. The precise tunability of these wrinkled stamps offers a high degree of freedom to create freely customized nanoparticle lattices.